2014
DOI: 10.1007/s10029-014-1261-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of single-port compared to multiport laparoscopic inguinal herniorraphy: a prospective randomized controlled study

Abstract: Compared to multiport, single-port laparoscopic total extraperitoneal inguinal herniorraphy, when performed by a high-volume and highly dedicated hernia surgeon, resulted in significantly reduced postoperative pain, analgesic requirements, quicker return to work/normal activities, improved cosmesis, and equivalent safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…In the field of hernia surgery, some specialized hernia centres have shown excellent safety and efficacy of SIL TEP repair. Our previous prospective randomized controlled study comparing singleport versus multiport TEP repair demonstrated unequivocal benefits of the single-port technique in terms of reducing post-op pain, analgesic requirements, earlier return to work or physical activities by 7 days and improved cosmetic scar scores [14]. Like any new invention, manufacturers need to recuperate Research and Development costs, and these single ports have remained relatively expensive compared to the conventional ports used for multiport surgery.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the field of hernia surgery, some specialized hernia centres have shown excellent safety and efficacy of SIL TEP repair. Our previous prospective randomized controlled study comparing singleport versus multiport TEP repair demonstrated unequivocal benefits of the single-port technique in terms of reducing post-op pain, analgesic requirements, earlier return to work or physical activities by 7 days and improved cosmetic scar scores [14]. Like any new invention, manufacturers need to recuperate Research and Development costs, and these single ports have remained relatively expensive compared to the conventional ports used for multiport surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Post-operatively, patients were contacted by phone on day one for an assessment of their pain score and they were seen on day 7 to assess wound healing, hernia recurrence (early failure), visual analogue pain score and the total number of pain killers ingested. They were then seen 6 weeks after surgery to assess them for return to work or normal physical activities, recurrence, length of umbilical incision and cosmetic scar score [3(least satisfied)-24(most satisfied)] [14]. We plan to follow-up these patients on an annual basis for 5 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations